Inclusive leadership and innovative work behavior: The role of psychological empowerment. (14th September 2018) - Javed, Basharat; Abdullah, Iqra; Zaffar, Muhmmad Adeel; Haque, Adnan ul; Rubab, Ume
Abstract: In this article, we explored the relationship between inclusive leadership and innovative work behavior with the mediating role of psychological empowerment. We collected data from employees in the information technology and cargo sectors within the United Kingdom and Canada. The results revealed that inclusive leadership was positively related to innovative work behavior both directly and indirectly through psychological empowerment. Cognitive evaluation theory was used to support the findings. Implications of the study were discussed.